(untitled) (diségno, 2021)
Katsuhiro Otomo (Hasama, 1954) is universally recognized as one of the masters of the Japanese comics industry. Akira (1982), a science fiction story set in a location characterized by endless skyscrapers, is certainly his most internationally known work. Two years before giving life to the world of Akira, Otomo laid the foundations for the creation of a coherent urban scenario in Dōmu, A Child’s Dream. Dōmu’s story is entirely set in an intensive Japanese condominium, a huge snake building called Tsutsumi Danchi. An architecture that Otomo represents in too much detail to be his own invention. The reference for Tsutsumi is in fact the Shibazono Danchi, a building of intensive housing located in the Saitama prefecture. Otomo, like an expert director, selects the location, distorting and shaping it to fit his vision. Through dramatic and highly detailed perspectives, Otomo makes the Tsutsumi Danchi one of the protagonists of the story. The paper aims to investigate how much drawing allows one to manipulate a simple suburban architecture to satisfy a creative vision. A dead inanimate object within the narrative becomes alive, pulsating with information. The drawing thus allows, like a cinematographic shot of a visionary author, to create a new world (tangential to the real one) but absolutely new and which has a life of its own.